Advances in the understanding of multiferroics through soft X-ray diffraction - Beale, T; Wilkins, S; Johnson, R; Prabhakaran, D; Boothroyd, A; Steadman, P; Dhesi, S; Hatton, P (2012)
The magneto-electric multiferroic TbMn 2O 5 has a complex magnetic structure in three different magnetically ordered phases. We have determined the nature of the induced magnetic order on the oxygen sites in the commensurate magnetic phase through full linear X-ray polarisation analysis at the oxygen K edge. This has been achieved rotating the linear polarisation of the incident beam at the source, and using multilayers to analyse the polarisation state of the scattered X-ray beam. We have confirmed that the anisotropy of the magnetic scattering at the oxygen edge is consistent with the anisotropy of the manganese magnetic structure. © 2012 EDP Sciences, Springer-Verlag.